PERENCANAAN PREVENTIVE MAINTENANCE MENGGUNAKAN METODE RELIABILITY PADA ELECTRICAL SISTEM AUXILIARY POWER UNIT BOEING 737-500 - Taaqbier, Mohammed; Setiawan, Ferry; Anhar, Muh (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2022)
The electrical system Auxiliary Power Unit on the Boeing 737-500 aircraft often experiences operational failure due to damage to the components in the system, this incident causes significant operational losses so that an appropriate maintenance method is needed to eliminate the factors that cause failure in the Electrical system Auxiliary Power Units. The purpose of this study is to plan preventive maintenance activities on the Electrical Auxiliary Power Unit system so that part damage that causes failure can be handled properly. The reliability method is calculated using the Weibull probability distribution so that the critical operating time limit is obtained on the Electrical Auxiliary Power Unit system. From the calculation results, the critical operational limit for the Electrical Auxiliary Power Unit system is 271 flight cycle with the main damage being the start relay component, with maintenance activities in the form of inspection, repair, testing and cleaning activities.